前日に均衡した方程式 |
3 K2O + Fe2(SO4)3 = 3 K2SO4 + Fe2O3
Zn(OH)2 + Na2(SO4) = ZnSO4 + NaOH =>
Zn(OH)2 + Na2(SO4) = ZnSO4 + 2 NaOH
C3H8 + O2 = CO2 + H2O =>
C3H8 + 5 O2 = 3 CO2 + 4 H2O
C5H20O + O2 = CO2 + H2O =>
2 C5H20O + 19 O2 = 10 CO2 + 20 H2O
C3H8 + O2 = CO2 + H2O =>
C3H8 + 5 O2 = 3 CO2 + 4 H2O
Cu(NO3)2 + NaOH = Cu(O2H2) + NaNO3 =>
Cu(NO3)2 + 2 NaOH = Cu(O2H2) + 2 NaNO3
H10C4O + O2 = H2O + H8C4O =>
2 H10C4O + O2 = 2 H2O + 2 H8C4O
Si + Fe3O4 = Fe2Si + Fe2O3 =>
Si + 6 Fe3O4 = Fe2Si + 8 Fe2O3
C6H5NO3 + FeCl3 = Fe(C6H4NO3)3 + HCl =>
3 C6H5NO3 + FeCl3 = Fe(C6H4NO3)3 + 3 HCl
H2O2 = O2 + (H)2O =>
2 H2O2 = O2 + 2(H)2O
H2SO4 + PbCl2 = PbSO4 + HCl =>
H2SO4 + PbCl2 = PbSO4 + 2 HCl
CH3COCOOH + [H] = CH3CHOHCH2OH + H2O =>
CH3COCOOH + 6[H] = CH3CHOHCH2OH + H2O
Sr + NaOH = Sr(OH)2 + Na =>
Sr + 2 NaOH = Sr(OH)2 + 2 Na
CO(g) + Br2(g) = COBr2(g) =>
CO(g) + Br2(g) = COBr2(g)
Al + ClH = AlCl3 + H2 =>
2 Al + 6 ClH = 2 AlCl3 + 3 H2
C10H8(s) + O2 = H2O(l) + CO2(g) =>
C10H8(s) + 12 O2 = 4 H2O(l) + 10 CO2(g)
Sb2S3(s) + Fe(s) = Sb2(s) + FeS3(s) =>
Sb2S3(s) + Fe(s) = Sb2(s) + FeS3(s)
Mg(NO3)2(aq) + CsBr(aq) = CsNO3(aq) + MgBr2(aq) =>
Mg(NO3)2(aq) + 2 CsBr(aq) = 2 CsNO3(aq) + MgBr2(aq)
CH3COOH + FeO = (CH3COO)2Fe + H2O =>
2 CH3COOH + FeO = (CH3COO)2Fe + H2O
CH3COOH + Fe(OH)3 = (CH3COO)3Fe + H2O =>
3 CH3COOH + Fe(OH)3 = (CH3COO)3Fe + 3 H2O
C2H9NaO5 + HCl = CH3COOH + NaCl + H2O =>
C2H9NaO5 + HCl = CH3COOH + NaCl + 3 H2O
Bi(OH)3 + K2SnO2 = Bi + K2 + SnO3 + H2O =>
2 Bi(OH)3 + 3 K2SnO2 = 2 Bi + 3 K2 + 3 SnO3 + 3 H2O
P + O2 = P2O5 =>
4 P + 5 O2 = 2 P2O5
NaClO + Fe(OH)3 + NaOH = NaCl + Na2(FeO3) + H2O =>
NaClO + 2 Fe(OH)3 + 4 NaOH = NaCl + 2 Na2(FeO3) + 5 H2O
HIO3 + H2SO3 = H2O + H2SO4 + I2 =>
2 HIO3 + 5 H2SO3 = H2O + 5 H2SO4 + I2
MeO + H2O = Me(OH)2 =>
MeO + H2O = Me(OH)2
Cu2O + H(NO3) = Cu(NO3)2 + NO + H2O =>
3 Cu2O + 14 H(NO3) = 6 Cu(NO3)2 + 2 NO + 7 H2O
C + KOH = CO2 + H2 + K =>
C + 2 KOH = CO2 + H2 + 2 K
H2O + NO2 = NH3 + O2 =>
6 H2O + 4 NO2 = 4 NH3 + 7 O2
*2K*Cl2 = *2KCl =>
*2K*Cl2 = *2KCl
Al + KCIO4 + H2SO4 = KCI + Al2(SO4)3 + H2O =>
8 Al + 3 KCIO4 + 12 H2SO4 = 3 KCI + 4 Al2(SO4)3 + 12 H2O
MnO4{-} + SO2 + H2O = Mn{+2} + SO4{-2} + H{+} =>
2 MnO4{-} + 5 SO2 + 2 H2O = 2 Mn{+2} + 5 SO4{-2} + 4 H{+}
Cu(NO3)2 + H2O = CuO + HNO3 =>
Cu(NO3)2 + H2O = CuO + 2 HNO3
LiOH + H2O = LiOHH2O =>
LiOH + H2O = LiOHH2O
H4P2O7 + Ba(OH)2 = (BaOH)4P2O7 + H2O =>
H4P2O7 + 4 Ba(OH)2 = (BaOH)4P2O7 + 4 H2O